The association between school climate, teacher emotions, and adaptive instruction - Kouhsari, Masoumeh; Huang, Xianhan; Wang, Chan; Lee, John Chi-Kin (Frontiers in Education, 2024)
IntroductionAlthough adaptive instruction has become increasingly important as a component of effective instruction, the mechanism of adaptive instruction remains underexplored. This study examined the potential associations between school climate and teacher emotions on adaptive instruction.MethodsThis study used cross-sectional approach with a sample included 2,880 primary school teachers from Chongqing, China.ResultsThe results indicated that of the five dimensions of school climate examined, teacher collaboration, student relations, and instructional innovation had positive and significant associations with adaptive instruction. Regarding teachers’ emotions, enjoyment was positively while anxiety was negatively associated with teachers’ adaptive instruction.DiscussionAs teachers’ positive emotions play important roles in adaptive instruction, policymakers and educators should focus on fostering teachers’ experiences of positive emotions. The finding of an adverse role of a teacher’s negative emotion in shaping adaptive instruction may be used in intervention programs and pieces of training for both pre-service and in-service teachers.